Pengembangan Teknologi Informasi Untuk Pengelolaan Koperasi Simpan Pinjam Di Nagori Bukit Rejo - Muklas Adi Putra; Romirza Arika; Zekrinaldi (JPM: Jurnal Pengabdian Masyarakat, 2023)
The current economic downturn makes people borrow money from loan sharks or other online loans that have very high interest rates. From this, the Nagori Bukit Rejo apparatus wants to provide a solution to this by running a savings and loan cooperative program, so that people are not trapped by loans. Savings and loan cooperatives are a type of business that prioritizes the interests of members to improve community welfare, this business is carried out by following Islamic law (shariah). So a system is needed to manage the savings and loan cooperative in Nagori Bukit Rejo, so a web and excel based system is designed. The web system is designed to be used as a web profile for Nagori Bukit Rejo and for managing data using Excel. This research aims to reduce people's risks from loan sharks or loan sharks, opening up sources of funds or capital for people who want to start MSME businesses. The system that has been designed will be utilized if the savings and loan cooperative program begins to operate in Nagori Bukit Rejo.